The political economy reader : contending perspectives and contemporary debates - Barma, Naazneen; Vogel, Steven Kent (New York : Brunner-Routledge, 2022)
"The Political Economy Reader advocates a particular approach to the study of political economy - the "market-institutional" perspective - which emphasizes the ways in which markets are embedded in political and social institutions. This perspective offers a compelling alternative to the market-liberal view, which advocates freer markets and less government intervention in the economy, as if states and markets were naturally at odds with each other. The reader embraces a truly interdisciplinary approach to the study of political economy, with extensive coverage from sociology, economics, history and political science. It includes some of the most important classical and contemporary theoretical perspectives on political economy. And it engages some of the most topical debates in political economy today, such as climate change, the global financial crisis, inequality, the digital platform economy, and the COVID-19 pandemic. For political economy courses at a variety of levels and from a range of disciplines, the reader is also of interest to scholars and citizens wanting perspective on the intersection of economics, politics, and society"--
Keywords: International economic relations; Capitalism